The impact of cut-soiler technology on rice-wheat production in salt-affected areas of western Indo-Gangetic Plains of India - Guenwoo Lee; Junya Onishi; Taishin Kameoka; Kayo Matsui; Gajender Yadav; Suresh Kumar; Govind Prasad; Satender Kumar; Rajender Kumar Yadav (PLoS ONE, 2025)
Soil salinization poses a significant challenge to agricultural productivity worldwide, particularly in the rice-wheat belt of the western Indo-Gangetic Plains (IGP), where excess sodium salts (sodicity) degrade soil health and threaten crop production. The cut-soiler, a farm machine developed in Japan, is an innovative and cost-effective solution. The cut-soiler constructs residue-filled, shallow subsurface drains, enhancing lateral and vertical water movement through the soil and improving soil conditions and crop productivity. Unlike previous studies confined to semi-controlled experimental settings, this research uniquely evaluates the effectiveness of cut-soiler technology on local farms severely affected by salinization, specifically addressing subsurface sodicity and recurrent waterlogging conditions that hinder agricultural profitability. From 2019 to 2023, feasibility trials were conducted in farmers’ fields across Punjab and Haryana, India, where gypsum was applied alongside crop residue to enhance subsurface soil reclamation. The analysis reveals significant improvements in the rice and wheat yields. The findings suggest that the application of a cut-soiler over an area of 20 hectares produces a positive net present value (NPV > 0), a benefit-cost ratio (BCR > 1), and an internal rate of return (IRR > 10%), thus supporting the financial viability of the investment for the reclamation of sodicity-affected regions. In addition, the cut-soiler reduces crop residue burning, contributing to environmental sustainability. The substantial yield increases observed in both experimental and conventional farming settings highlight the potential of cut-soiler technology to transform agricultural practices in salt-affected regions, improve crop productivity, and boost economic returns for local farmers.